Microbiota dysbiosis influences immune system and muscle pathophysiology of dystrophin‐deficient mice - Andrea Farini; Luana Tripodi; Chiara Villa; Francesco Strati; Amanda Facoetti; Guido Baselli; Jacopo Troisi; Annamaria Landolfi; Caterina Lonati; Davide Molinaro; Michelle Wintzinger; Stefano Gatti; et al. (EMBO Molecular Medicine)
Abstract Duchenne muscular dystrophy (DMD) is a progressive severe muscle‐wasting disease caused by mutations in DMD, encoding dystrophin, that leads to loss of muscle function with cardiac/respiratory failure and premature death. Since dystrophic muscles are sensed by infiltrating inflammatory cells and gut microbial communities can cause immune dysregulation and metabolic syndrome, we sought to investigate whether intestinal bacteria support the muscle immune response in mdx dystrophic murine model. We highlighted a strong correlation between DMD disease features and the relative abundance of Prevotella. Furthermore, the absence of gut microbes through the generation of mdx germ‐free animal model, as well as modulation of the microbial community structure by antibiotic treatment, influenced muscle immunity and fibrosis. Intestinal colonization of mdx mice with eubiotic microbiota was sufficient to reduce inflammation and improve muscle pathology and function. This work identifies a potential role for the gut microbiota in the pathogenesis of DMD.